Structure and thrusting evolution of the southern Cordillera Oriental (N Argentine Andes) - Carrera, N.; Muñoz, J. A. (TRABAJOS DE GEOLOGÍA, 2009)
Detailed mapping of several areas of the southern Cordillera Oriental revealed an important role of the inversion tectonics for the structural evolution of this part of the Andes. The inversion is only moderate but the compressional Andean structures are strongly controlled by the geometry and the location of previous cretaceous extensional structures. The study of growth strata and unconformities in the Cenozoic synorogenic sediments provides evidence for the eastward migration of the Andean deformation from the Puna to the Santa Bárbara System independently of the vergence of the structures.